2015
DOI: 10.1007/s40520-015-0337-0
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of frailty and related factors in community-dwelling Turkish elderly according to modified Fried Frailty Index and FRAIL scales

Abstract: According to both scales, frailty was strongly associated with cognitive impairment, depressive mood, and malnutrition in the community-dwelling Turkish elderly population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
4
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 22 publications
6
52
4
4
Order By: Relevance
“…Physically frail adults (SPPB grade 3) had a higher adjusted risk of FoF compared to less physically frail adults. Contrary to the findings of the present study, a population-based study on 906 community-dwelling older Turkish adults (71.5 ± 5.6 years; 50.6% female) indicated that physical frailty assessed with Fried et al's scale was not associated with FoF in the multivariate model [23].…”
Section: Discussioncontrasting
confidence: 99%
“…Physically frail adults (SPPB grade 3) had a higher adjusted risk of FoF compared to less physically frail adults. Contrary to the findings of the present study, a population-based study on 906 community-dwelling older Turkish adults (71.5 ± 5.6 years; 50.6% female) indicated that physical frailty assessed with Fried et al's scale was not associated with FoF in the multivariate model [23].…”
Section: Discussioncontrasting
confidence: 99%
“…Advanced age, lower education level (lower than university level), dementia, depression, poorer nutritional status, poorer activities of daily living, falls, lower handgrip strength were shown to be strongly and independently associated factors for frailty in our study. These results support the findings in the literature (6)(7)(8)(20)(21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the prevalence of frailty of older adults in the geriatric outpatient clinic was similar to the frailty rates in European countries, lower than the Physical Medicine and Rehabilitation outpa- tient clinics patients and higher than older people living in the rural area in Turkey (5,7).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Based on the identification of the factors associated with the fear of falling in the older adult, it is possible to get an overview that can help in the development of actions aimed not only at the target audience but also actions involving health professionals who deal with the older adult, their relatives and caregivers (8)(9) . The relevance of the study is based on the premise that knowledge about the factors associated with fear of falls is crucial, since falls of the older adult are an important public health problem and one of the main causes of mental health and QoL impairment in this population (1) .…”
Section: Introductionmentioning
confidence: 99%